PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Satriadi, Dimas (Jurnal Benefita, 2016)
In an organization , success or failure to the performance of duties and the implementation of , influenced by leadership , through leadership and supported by organisational capacity adequate , so the good governance ( good governance ) be called off , in contrast weakness leadership is one of the reasons of the destruction of performance of the bureaucracy in indonesia .Research aims to understand the influence of leadership the school principal of the performance of teacher at junior high schools 7 tanjungpinang .The kind of research done is associative with the quantitative approach .This research do in the city tanjungpinang especially in junior high schools 7 tanjungpinang .In this research that will be the population and sample is a head of school and teachers junior high schools 7 tanjungpinang which consisted of 45 people In this research technique and an instrument the collection of the data used was interviews and questionnaires .Measurement techniques used in this research is likert scale .Analysis of the technique used is a technique analysis of the statistics parametris as the form of research is associative , with employing correlation bivariate / product moment pearson .The result of this research is that there a correlation / relationship which is very strong between variables leadership the school principal ( x ) , with the performance of teachers in public junior high schools as much as 7 tanjungpinang 0,826 or have a direct impact of 68,2 % .That means that if the leadership of the head of the school is good that the performance of teachers also look good Keywords: Leadership, Performance